'Dry' and 'wet' cough: how reliable is parental reporting?. Issue 1 (22nd May 2019) - Donnelly, Deirdre; Everard, Mark L
Abstract : Introduction: Chronic cough in childhood is common and causes much parental anxiety. Eliciting a diagnosis can be difficult as it is a non-specific symptom indicating airways inflammation and this may be due to a variety of aetiologies. A key part of assessment is obtaining an accurate cough history. It has previously been shown that parental reporting of 'wheeze' is frequently inaccurate. This study aimed to determine whether parental reporting of the quality of a child's cough is likely to be accurate. Methods: Parents of 48 'new' patients presenting to a respiratory clinic with chronic cough were asked to describe the nature of their child's cough. They were then shown video clips of different types of cough using age-appropriate examples, and their initial report was compared with the types of cough chosen from the video. Results: In a quarter of cases, the parents chose a video clip of a 'dry' or 'wet' cough having given the opposite description. In a further 20% parents chose examples of both 'dry' and 'wet' coughs despite having used only one descriptor. Discussion: While the characteristics of a child's cough carry important information that may be helpful in reaching a diagnosis, clinicians should interpret parental reporting of the nature of a child's cough with some caution in that one person's 'dry' cough may very well be another person's 'wet' cough.